A Practical Review for Cardiac Rehabilitation Professionals of Continuous-Flow Left Ventricular Assist Devices. Issue 5 (September 2015) - Compostella, Leonida; Russo, Nicola; Setzu, Tiziana; Bottio, Tomaso; Compostella, Caterina; Tarzia, Vincenzo; Livi, Ugolino; Gerosa, Gino; Iliceto, Sabino; Bellotto, Fabio
<x xml:space="preserve">Abstract</x> An increasing number of patients with end-stage heart failure are being treated with continuous-flow left ventricular assist devices (cf-LVADs). These patients provide new challenges to the staff in exercise-based cardiac rehabilitation (CR) programs. Even though experience remains limited, it seems that patients supported by cf-LVADs may safely engage in typical rehabilitative activities, provided that some attention is paid to specific aspects, such as the presence of a short external drive line. In spite of initial physical deconditioning, CR allows progressive improvement of symptoms such as fatigue and dyspnea. Intensity of rehabilitative activities should ideally be based on measured aerobic capacity and increased appropriately over time. Regular, long-term exercise training results in improved physical fitness and survival rates. Appropriate adjustment of cf-LVAD settings, together with maintenance of adequate blood volume, provides maximal output, while avoiding suction effects. Ventricular arrhythmias, although not necessarily constituting an immediate life-threatening situation, deserve treatment as they could lead to an increased rate of hospitalization and poorer quality of life. Atrial fibrillation may worsen symptoms of right ventricular failure and reduce exercise tolerance. Blood pressure measurements are possible in cf-LVAD patients only using a Doppler technique, and a mean blood pressure ⩽80 mmHg is considered "ideal." Some patients may present with orthostatic intolerance, related to autonomic dysfunction. While exercise training constitutes the basic rehabilitative tool, a comprehensive intervention that includes psychological and social support could better meet the complex needs of patients in which cf-LVAD may offer prolonged survival.